Inflammation-Generated Extracellular Matrix Fragments Drive Lung Metastasis. (20th December 2017) - Bekaert, Sandrine; Fillet, Marianne; Detry, Benoit; Pichavant, Muriel; Marée, Raphael; Noel, Agnes; Rocks, Natacha; Cataldo, Didier
Mechanisms explaining the propensity of a primary tumor to metastasize to a specific site still need to be unveiled, and clinical studies support a link between chronic inflammation and cancer dissemination to specific tissues. Using different mouse models, we demonstrate the role of inflammation-generated extracellular matrix fragments ac-PGP ( N -acetyl-proline-glycine-proline) on tumor cells dissemination to lung parenchyma. In mice exposed to cigarette smoke or lipopolysaccharide, lung neutrophilic inflammation produces increased levels of MMP-9 (matrix metalloproteinase 9) that contributes to collagen breakdown and allows the release of ac-PGP tripeptides. By silencing CXCR2 gene expression in tumor cells, we show that these generated ac-PGP tripeptides exert a chemotactic activity on tumor cells in vivo by binding CXCR2.